1994
DOI: 10.1257/jep.8.4.145
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transfers and the Accumulation of Wealth

Abstract: This paper uses household data to provide direct estimates of intergenerational transfers as a source of wealth. The authors distinguish between intended transfers (for example, gifts to other households) and possibly unintended transfers (bequests) and estimate that intended transfers account for at least 20 percent of net worth. Thus, a significant portion of the U.S. wealth cannot be explained by the life-cycle model, even when the model is augmented to allow for bequests. Estimated bequests can account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
254
2
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(267 citation statements)
references
References 10 publications
(10 reference statements)
8
254
2
3
Order By: Relevance
“…Empirical evidence provided by studies such as Cox and Raines (1985) and Gale and Scholz (1994) does indeed suggest that there is substantial underreporting of private transfers, and particularly so for transfers received. As noted by Kessler and Masson (1989, p. 148), this might be attributed to "people's tendency to admit more easily that they have given than that they have received".…”
Section: The Effect Of Religiosity On Income Inequalitymentioning
confidence: 97%
See 1 more Smart Citation
“…Empirical evidence provided by studies such as Cox and Raines (1985) and Gale and Scholz (1994) does indeed suggest that there is substantial underreporting of private transfers, and particularly so for transfers received. As noted by Kessler and Masson (1989, p. 148), this might be attributed to "people's tendency to admit more easily that they have given than that they have received".…”
Section: The Effect Of Religiosity On Income Inequalitymentioning
confidence: 97%
“…In this paper, the results we report use the "belief in afterlife" index reported by the World Values Survey conducted in 2000 as the relevant measure of religiosity due to its proximity to our theoretical modeling of religion in the previous section. 12 As the measure of inequality, we use the Gini index from the UNDP. The data on tax burden, government spending to GDP ratio, and transfers to GDP ratio come from Government Finance Statistics of the IMF.…”
Section: Datamentioning
confidence: 99%
“…They concluded that intergenerational transfers were not an important source of wealth, even for rich families. However, Gale and Scholz (1994), using the 1983 Survey of Consumer Finances, estimated that at least 51 percent of household wealth was accounted for by inheritances and other "intentional" wealth transfers. Brown and Weisbenner (2004), using the 1998 SCF, estimated that 19 percent of households that year received some kind of wealth transfers (this is very close to our own estimate) and that one fifth to one fourth of aggregate household wealth was traceable to wealth transfers, depending on the interest rate used to capitalize past inheritances.…”
Section: Literature Review On Inheritancesmentioning
confidence: 99%
“…For the relevance of intergenerational transfers in general concerning household savings, see Kotlikoff (1988). Gale and Scholz (1994) identify transfers from parents to their children as the major part of intergenerational household transfers. 55 There is a vast literature on the employment patterns of single parents compared to couple households, see e.g.…”
Section: Effects Of Income Uncertainty On the Consumption-savings Decmentioning
confidence: 99%